Nationalist Pluralism in Fiqh Sosial: Ideas and Actions of KH. MA. Sahal Mahfudh - Arif Chasannudin; Jamal Ma'mur Asmani (Santri: Journal of Pesantren and Fiqh Sosial, 2020)
This study explores the ideas and actions of KH. MA Sahal Mahfudh's pluralism as a role model for society. This qualitative descriptive research used fiqh sosial as a tool of analysis. The data is derived from the different works of Kiai Sahal and other supporting works are complemented by interviews with figures who understand the thinking of Kiai Sahal. The results of research on the thoughts and practices of Kiai Sahal on pluralism are fiqh ikhtilaf, the basic principle of pluralism that promotes tolerance, and the state does not need to be labeled Islam. Meanwhile, Kiai Sahal's pluralism practices include accepting Pancasila, fighting for non-Muslim burials, allowing non-Muslims to teach in pesantren, engaging in interfaith cooperation, prohibiting hostility to non-Muslims, and differentiating between religious areas and mu'amalah. Kiai Sahal's contribution to the aspect of thinking is to open up the inclusiveness of thought while in fact, it can enhance the diversity of the country. Based on this research, Kiai Sahal Mahfudh's pluralism style is nationalist pluralism.